Evaluación técnico financiera del aprovechamiento de energía hidrocinética en el calentamiento eléctrico de ductos Pipe-in-Pipe para el control de formación de hidratos en agua ultraprofundas, caso de estudio: Presal-Comperj Rota 3 en el sudeste brasilero (2022)
In this case study, a technical-financial evaluation of the use of tidal energy in the heating of Pipe-in-Pipe pipelines is carried out as a measure to control hydrate formation in the ultra-deep water zone of the Brazilian coast. As an alternative energy mechanism in direct electrical heating in pipelines, the energy conversion of waves is used, which is becoming of interest due to offshore exploration in the oil industry.